Bibliometric analysis on pharmaceutical care publications in Southeast Asia: prospective research trends - Riyadi, Rahmat; Alfian, Sofa Dewi (Faculty of Pharmacy, Universitas Pancasila, 2025)
Studies related to bibliometric analysis have been conducted globally to determine the development of pharmaceutical care. However, the prospective trends of scientific research associated with pharmaceutical care in Southeast Asia remain unclear. This study sets out to analyze and compare the results of pharmaceutical care research in Southeast Asian countries in terms of bibliometric indices. An investigation on the main electronic database Scopus was conducted for research purposes on pharmacy care in Southeast Asia until August 6, 2023. The analysis derived from the investigation included an evaluation of published document by year; lead author; country or territory, institutional affiliation, document type, subject area analysis; citation and co-citation analysis; journals that published the most articles, and the most researched topics. Microsoft Excel and VOSviewer were utilized to conduct a qualitative analysis on this dataset. This study adopted the co-authorship analysis, co-citation analysis and keyword analysis in order to gain an insight onto the research prospects and trends in pharmaceutical care. A total of 1,261 studies correlating to pharmaceutical care in Southeast Asia met the criteria for qualitative analysis. The top three countries with the highest number of publications were Malaysia, Thailand and Indonesia. Malaysia had the highest citation count (n=4670, 27.45%), followed by Thailand (n=3292, 19.35%), and Vietnam (n=3096, 18.20%). From networks of co-authorship analysis of authors, there were no collaborations found among authors in Southeast Asia. Prospective research analyzing keywords related to the theme of pharmaceutical care includes pharmacy practice, medication adherence, and qualitative research. Bibliometric analysis provides a comprehensive view of the field and status of pharmaceutical care research to develop prospective future trends and collaborations in Southeast Asia. A bibliometric analysis suggests that stronger teamwork among Southeast Asian researchers is crucial for future advancements.